Observations sur la dynamique du développement du Diplodia mutila Fr. apud Mont. sur le chêne-liège, Quercus suber L., au Maroc (Cryptogamie Mycologie, 2000)
Mamora forest in Rabat (Morocco) was a wide forest of cork oak which is rapidly disappearing. This crisis is caused by both human exploitation and overgrazing by animals. This situation is also affected by the existence of harmful insects and parasitic fungi. One of the most common species is Diplodia mutila Fr. apud Mont. (group of Coelomycetes) anamorph of Botryosphaeria stevensii Shoem., which causes withering and cankers on trunks and branches. The electron microscope observations on pycnosporogenesis and the study of the relation plant-host-pathogen show the structure and the biological cycle of Diplodia mutila, the endophytic and the systemic development of the pathogen and the irreversible damage on the plant host. This study is a contribution to the research on cork-oak forest protection.